Estimating the Level and Distribution of Global Wealth, 2000–2014. (18th August 2017) - Davies, James B.; Lluberas, Rodrigo; Shorrocks, Anthony F.
Abstract : This paper estimates the level and distribution of household wealth globally, as well as for regions and countries, for the period 2000–2014. The data used are mainly from household surveys and national accounts balance sheets, covering about two thirds of the world's population and over 95% of global household wealth. Lists of the most wealthy published in the media are used to adjust the upper tail. Wealth levels and distributions are imputed for countries without data. Estimated global household wealth stood at USD 251 trillion in 2014, having grown from USD 117 trillion in the year 2000. Wealth per adult in 2014 was USD 53, 000. The estimated Gini coefficient of global wealth was 92.2% in 2014 and the share of the top 10% was 88.3%. Wealth inequality fell from 2000 to 2007, with the share of the top 10% falling from 89.4% to 86.5%, before rising steadily to 2014. From 2000 to 2008 the share of financial assets in gross wealth, an important driver of wealth inequality, fell from 55.2% to 50.2%, before climbing to 55.0% in 2014. Household debt rose from 13.6% of gross assets in 2000 to 16.0% in 2008, and has since fallen to 13.9%.